The geometry of information retrieval - Van Rijsbergen, C. J., 1943- (Cambridge University Press, 2004)
The author shows how different models of information retrieval can be combined in the same framework used to formulate quantum mechanics. The relation with quantum computing is also examined. Appendices with background on physics and mathematics are included. This is an important, ground-breaking book, with much new and original material.